Australian local government action on climate change adaptation: some critical reflections to assist decision-making - Kennedy, Deborah; Stocker, Laura; Burke, Gary (Routledge, 2010)
The primary objective of this paper is to discuss the limitations of risk management as a strategy for Australian local government climate change adaptation and explore the advantages of complementary approaches, including a social-ecological resilience framework, adaptive and transition management, and vulnerability assessment. Some federal and local government initiatives addressing the limitations of risk-based approaches are introduced. We argue that conventional risk-based approaches to adaptation, largely focused on hazard identification and quantitative modelling, will be inadequate on their own for dealing with the challenges of climate change. We suggest that responses to climate change adaptation should move beyond conventional risk-based strategies to more realistically account for complex and dynamically evolving social-ecological systems.